The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.6007/ijarbss/v8-i8/4633
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Public Expenditure for Technical and Vocational Education and Employability Skills of the Graduates of Vocational Colleges in Malaysia

Abstract: Public expenditure for technical and vocational education is important for Malaysia to produce high skilled workers to achieve the status of a developed and high-income country by the year 2020. The objective of this study is to measure the relationship between public expenditure for technical and vocational education and employability skills of the graduates of vocational colleges in Malaysia. The SmartPLS path model analysis revealed two important findings: first, recurrent expenditure was significantly corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Ali et al, [12] carried out a study to determine the relationship between public expenditure for TVET and employability skills of the graduates of vocational colleges in Malaysia. The methodology was crosssectional research design which permitted the researcher to integrate public expenditure for education literature review and questionnaires to collect data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al, [12] carried out a study to determine the relationship between public expenditure for TVET and employability skills of the graduates of vocational colleges in Malaysia. The methodology was crosssectional research design which permitted the researcher to integrate public expenditure for education literature review and questionnaires to collect data.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reviewed revealed that numerous studies in budget adequacy and student enrolment in TVET institutions have been carried out. Some of these include; Kipyego [4], Rabia et al, [7], Alecke et al, [13], Anyanua & Erhijakpor [5], Ali et al, [12] and Ivo & Prasetyia [11]. However the studies did not specifically address the relationship between budget adequacy and student enrolment.…”
Section: Introductionmentioning
confidence: 99%